Religiousity Choosen: Was It Affected to Young Generation’s Election Behavior? - Abdullah, Mulyana; Hakam, Kama A; Wilodati, Wilodati; Ratnafitria, Ratnafitria (Universitas Ahmad Dahlan, 2019)
To assess the influence of religious faith, especially Islam, to the point of view and election behavior on the young generation, this research is focused upon UPI students was carried out by applying the associative causal method and quantitative approach. By taking samples to youngest students as voter novice which is determined by probability sampling, the result proved that there is a significant influence of the religious aspect to election behavior among students of UPI. But, it seems that religious faith isn?t a dominant factor. It can be seen from how major of the influence of religious faith to the election behavior was only 11.9 %. So that, it is recommended that as the effort to give political understanding and implementation for young generations of Moslem, religion need to be implemented holistically, not partial, to avoid misinterpretation on Islamic terms and laws that as the basis of the political participation process.